Eight new species of the genus Nesamblyops Jeannel (Anillini: Carabidae: Coleoptera) from New Zealand with notes about dispersal of the genus to the North Island - Sokolov, Igor M. (Zootaxa, 2023)
Species of flightless litter ground beetles of the tribe Anillini, genus Nesamblyops, from the North Island and from the north-eastern part of the South Island are revised. Eight new species are described and one previously known species, Nesamblyops oreobius (Broun), is re-described. Nesamblyops oreobius, the only hitherto recorded species from the North Island, is most similar to the group of two new species from the South Island, N. confusus n. sp. (type locality: New Zealand, Marlborough Sounds, Mount Stokes) and N. lescheni n. sp. (type locality: New Zealand, Marlborough Sounds, D’Urville Island), based on the structure of the male genitalia. The second species of the genus known from the North Island, N. tararua n. sp. (type locality: New Zealand, Wellington, Tararua Range) represents another lineage, based on the structure of the male genitalia, and is closely related to a group of three new species from the South Island, N. brouni n. sp. (type locality: New Zealand, Canterbury, Southern Alps, Lewis Pass), N. distinctus n. sp. (type locality: New Zealand, Marlborough, Richmond Range, Fabians Valley), and N. townsendi n. sp. (type locality: New Zealand, Marlborough Sounds, Tennyson Inlet). Nesamblyops carltoni n. sp. (type locality: New Zealand, Nelson, Richmond Range, Dun Mountain) and N. parvulus n. sp. (type locality: New Zealand, Marlborough Sounds, Mount Stokes), both from the South Island occupy an isolated position among the examined species. All species are illustrated with digital images of habitus, body parts, and drawings of genitalia. Distribution maps for all species are also provided. Geographical evidence of Nesamblyops dispersal to the North Island is discussed, based on distributional data.